Influence of Eu3+-Doped on Phase Transition Kinetics of Pseudoboehmite. (3rd October 2013) - Zhu, Fuliang; Meng, Yanshuang
Abstract : The influence of Eu 3+ -doped on phase transition kinetics of pseudoboehmite has not been reported in the literature. Through dropping Eu(NO3 )3 into pseudoboehmite colloidal solution, pseudoboehmite xerogel was produced using spray pyrolysis. The influence of Eu 3+ -doped on the mechanism of pseudoboehmite phase transition kinetics has been calculated and analyzed by TG/DSC, XRD, and Kissinger equation. Part of Eu 3+ ion formed compound EuAl12 O19, which existed between α -Al2 O3 grains. Bulk diffusion of Al 3+ was prevented from compound EuAl12 O19 . Therefore, phase transition kinetics rate of θ -Al2 O3 → α -Al2 O3 was slowed down, causing an increase of phase transition activation energy and elevation of phase transition temperature.